Exposure and behavioral responses of tagged beluga whales ( Delphinapterus leucas ) to ships in the Pacific Arctic - Morgan J. Martin; William D. Halliday; Luke Storrie; John J. Citta; Jackie Dawson; Nigel E. Hussey; Francis Juanes; Lisa L. Loseto; Shannon A. MacPhee; Lisa Moore; Adrian Nicoll; Gregory O'Corry‐Crowe; et al. (Marine Mammal Science, 2023)
Arctic marine mammals face a multitude of challenges linked to climate change, including increasing anthropogenic noise from ship traffic. The beluga whale ( Delphinapterus leucas ), a predominately Arctic endemic cetacean, relies heavily on acoustic communication, with documented overlap between their vocalizations and hearing range and ship noise. Some belugas migrate through areas with the highest levels of ship traffic in the Pacific Arctic and exposure to ship noise is highly probable. Here, we document the responses of nine satellite‐tagged Eastern Beaufort Sea belugas to encounters with ships in the Beaufort, Chukchi, and Bering Seas during July–December 2018. We report 177 occasions when ships were within 125 km of tagged belugas and quantified changes in lateral and vertical movements to investigate individual behavioral responses to ship approaches within 50 km ( n = 23). Belugas' swim speed was negatively correlated with ship distance, showing possible changes in swim speed up to 79 km away. Changes in lateral and vertical movements, indicating disruption of behavior, were observed when some ships passed within 50 km. These findings corroborate previous studies that have shown behavioral responses of belugas to ships at distances far beyond visual range, implying belugas react to low‐amplitude ship noise near ambient levels.

Impact of quorum sensing from native peanut phosphate solubilizing Serratia sp. S119 strain on interactions with agronomically important crops - Cinthia Tamara Lucero; Graciela Susana Lorda; Nigel Halliday; Mariela Lis Ambrosino; Miguel Cámara; Tania Taurian (Symbiosis, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The impaired quorum sensing response of Pseudomonas aeruginosa MexAB‐OprM efflux pump overexpressing mutants is not due to non‐physiological efflux of 3‐oxo‐C12‐HSL - Manuel Alcalde‐Rico; Jorge Olivares‐Pacheco; Nigel Halliday; Miguel Cámara; José Luis Martínez (Environmental Microbiology, 2020)
Summary Multidrug (MDR) efflux pumps are ancient and conserved molecular machineries with relevant roles in different aspects of the bacterial physiology, besides antibiotic resistance. In the case of the environmental opportunistic pathogen Pseudomonas aeruginosa , it has been shown that overexpression of different efflux pumps is linked to the impairment of the quorum sensing (QS) response. Nevertheless, the causes of such impairment are different for each analysed efflux pump. Herein, we performed an in‐depth analysis of the QS‐mediated response of a P. aeruginosa antibiotic resistant mutant that overexpresses MexAB‐OprM. Although previous work claimed that this efflux pump extrudes the QS signal 3‐oxo‐C12‐HSL, we show otherwise. Our results evidence that the observed attenuation in the QS response when overexpressing this pump is related to an impaired production of alkyl quinolone QS signals, likely prompted by the reduced availability of one of their precursors, the octanoate. Together with previous studies, this indicates that, although the consequences of overexpressing efflux pumps are similar (impaired QS response), the underlying mechanisms are different. This 'apparent redundancy' of MDR efflux systems can be understood as a P. aeruginosa strategy to keep the robustness of the QS regulatory network and modulate its output in response to different signals.

Biotic inactivation of the P seudomonas aeruginosa quinolone signal molecule - Eliza Ye‐Chen Soh; Siri R. Chhabra; Nigel Halliday; Stephan Heeb; Christine Müller; Franziska S. Birmes; Susanne Fetzner; Miguel Cámara; Kok‐Gan Chan; Paul Williams (Environmental Microbiology, 2015)
Summary In P seudomonas aeruginosa , quorum sensing ( QS ) regulates the production of secondary metabolites, many of which are antimicrobials that impact on polymicrobial community composition. Consequently, quenching QS modulates the environmental impact of P . aeruginosa . To identify bacteria capable of inactivating the QS signal molecule 2‐heptyl‐3‐hydroxy‐4(1 H )‐quinolone ( PQS ), a minimal medium containing PQS as the sole carbon source was used to enrich a M alaysian rainforest soil sample. This yielded an A chromobacter xylosoxidans strain ( Q 19) that inactivated PQS , yielding a new fluorescent compound ( I ‐ PQS ) confirmed as PQS ‐derived using deuterated PQS . The I ‐ PQS structure was elucidated using mass spectrometry and nuclear magnetic resonance spectroscopy as 2‐heptyl‐2‐hydroxy‐1,2‐dihydroquinoline‐3,4‐dione ( HHQD ). A chromobacter xylosoxidans Q 19 oxidized PQS congeners with alkyl chains ranging from C 1 to C 5 and also N ‐methyl PQS , yielding the corresponding 2‐hydroxy‐1,2‐dihydroquinoline‐3,4‐diones, but was unable to inactivate the PQS precursor HHQ . This indicates that the hydroxyl group at position 3 in PQS is essential and that A . xylosoxidans inactivates PQS via a pathway involving the incorporation of oxygen at C 2 of the heterocyclic ring. The conversion of PQS to HHQD also occurred on incubation with 12/17 A . xylosoxidans strains recovered from cystic fibrosis patients, with P . aeruginosa and with A rthrobacter , suggesting that formation of hydroxylated PQS may be a common mechanism of inactivation.